2021
DOI: 10.3390/cancers13030449
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNA Panel as a Potential Novel Biomarker for Oral Squamous Cell Carcinoma Diagnosis

Abstract: A lack of reliable biomarkers for oral squamous cell carcinoma (OSCC) poses a major clinical issue. The sensitivity and specificity of classical serum tumor markers, such as the squamous cell carcinoma antigen (SCC-Ag), are quite poor, especially for early detection. This study aimed to identify specific serum miRNAs potentially serving as OSCC biomarkers. The expression levels of candidate miRNAs in serum samples from 40 OSCC patients and 40 healthy controls were quantitatively analyzed via microarray and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
(54 reference statements)
2
12
1
Order By: Relevance
“…Employing the asymmetric electrolyte conditions, three types of output duplex-detection signals were observed even when using clinical samples (Figure S12). The signals could be classified based on the reference data; however, the experimentally obtained abundance ratio of the output duplexes conflicted with the miRNA profiling trends in the previous report; 29 our data indicated under-expression of both miR-19a and miR-5100 in OSCC patients (Figure S12).…”
Section: Design Of Diagnostic Dna Probes and Simulatedcontrasting
confidence: 89%
See 2 more Smart Citations
“…Employing the asymmetric electrolyte conditions, three types of output duplex-detection signals were observed even when using clinical samples (Figure S12). The signals could be classified based on the reference data; however, the experimentally obtained abundance ratio of the output duplexes conflicted with the miRNA profiling trends in the previous report; 29 our data indicated under-expression of both miR-19a and miR-5100 in OSCC patients (Figure S12).…”
Section: Design Of Diagnostic Dna Probes and Simulatedcontrasting
confidence: 89%
“…According to the quantitative analysis, the over-(miR-19a) and under-(miR-5100) expression level was determined to be 2-and 0.5-fold, respectively. 29 simultaneous pattern recognition of these miRNAs, we here utilized sequence design for DNA-based parallel computation 1,20 and designed dgDNAs, which consisted of a partially complementary sequence with target miRNAs (Figure 1b). As a proof of concept, four expression patterns of target miRNAs were prepared involving over/under-expression, and we thermodynamically simulated the molecular computation using nanomolar concentrations of oligonucleotides (described in detail in the Experimental Section).…”
Section: Design Of Diagnostic Dna Probes and Simulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence analysis and outlier detection identified several outlier individual studies. After excluding seven outliers ( 34 , 38 , 41 , 47 , 48 ), the I 2 for heterogeneity decreased both in sensitivity (from 91.49% to 84.30%) and specificity (from 89.17% to 84.31%). However, the overall results showed only minimal changes and were similar to the original ones as the pooled specificity of the overall study increased from 0.76 to 0.78, PLR increased from 3.2 to 3.4, DOR decreased from 9 to 10, and AUC increased from 0.82 to 0.83, while sensitivity and NLR had no changes.…”
Section: Resultsmentioning
confidence: 97%
“…The model could identify 13 cancer types with high accuracy. Regarding the early detection of oral cancer, Nakamura et al found that serum miRNA expression signatures, including miR-19a, miR-20a, and miR-5100, could distinguish between OSCC patients and healthy donors with high diagnostic accuracy [ 20 ]. Romani et al conducted a microarray analysis of salivary miRNAs and identified 25 miRNAs expressed differently between OSCC patients and healthy controls [ 21 ].…”
Section: Liquid Biopsy For Cancer Detectionmentioning
confidence: 99%